(untitled) (Al-Quds Journal for Natural Sciences, 2021)
Imagination is more important than knowledge when knowledge is limited and cannot solve important questions. Inventiveness in the drug design has been clumsiness in quality and quantity. This may be due to the ineptness and incapability of medicinal chemists to comprehend biochemistry and biology issues. On the other hand, biochemists, biologists, and pharmaceutical chemists do not possess the expertise to make complex organic entities. Hence, a team comprising of all expertise is a must to invoke a novel drug. Drug discovery and development is expensive and time-consuming since it consists of many steps that start with target and lead discovery and end with human clinical trials. The estimation is that about 10-15 years are needed to present a new drug to the market with a cost of 1-1.5 billion dollars (Figure 1), (Karaman 2014 a,b). During the recent few decades, considerable attention has been focused on improving the pharmacokinetics of existing marketed drugs, thus providing new organic entities capable of providing more e!ciency with fewer drawbacks than their corresponding parent drugs. Among the approaches that can fulfill the requirements for invoking therapeutics with optimum absorption, distribution, metabolism, and excretion (ADME) properties is the prodrug approach.